2005
DOI: 10.1038/sj.cdd.4401756
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between p53 and p130(Rb2) in induction of cellular senescence

Abstract: To determine pathways cooperating with p53 in cellular senescence when the retinoblastoma protein (pRb)/p16INK4a pathway is defunct, we stably transfected the p16INK4a-negative C6 rat glioma cell line with a temperature-sensitive mutant p53. Activation of p53 induces a switch in pocket protein expression from pRb and p107 to p130(Rb2) and stalls the cells in late G1, early S-phase at high levels of cyclin E. Maintenance of the arrest depends on the functions of p130(Rb2) repressing cyclin A. Inactivation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
7
43
0
Order By: Relevance
“…Levels of cyclin E, p27 KIP1 and p21 CIP1 increased, whereas cyclin A was repressed (Kapic et al, 2006). A similar sequence of events was induced by overexpression of Rb2/p130 in JC virus-induced hamster brain tumor cells (Howard et al, 2000).…”
Section: The Rb2/p130-mediated Growth Arrest In Cellular Senescencementioning
confidence: 67%
See 2 more Smart Citations
“…Levels of cyclin E, p27 KIP1 and p21 CIP1 increased, whereas cyclin A was repressed (Kapic et al, 2006). A similar sequence of events was induced by overexpression of Rb2/p130 in JC virus-induced hamster brain tumor cells (Howard et al, 2000).…”
Section: The Rb2/p130-mediated Growth Arrest In Cellular Senescencementioning
confidence: 67%
“…Although not proven formally, this may also explain the decrease in p107 and pRb/105 expression subsequent to the appearance of Rb2/p130 in cellular senescence induced by p53 (Kapic et al, 2006). Alternatively, p53 itself may block pRb/p105 expression via a p53 binding site in the pRb/p105 promoter (Shiio et al, 1992;Osifchin et al, 1994).…”
Section: The Rb2/p130-mediated Growth Arrest In Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…To perform this task, these 'pocket proteins' utilize mechanisms mostly related to inactivation of transcription factors (Kouzarides, 1995), such as those of the E2F family (Cao et al, 1992;Helin et al, 1992Helin et al, , 1993Shirodkar et al, 1992;Beijersbergen et al, 1994;Hijmans et al, 1995;Sardet et al, 1995;Hurford et al, 1997), that promote the cell entrance into the S phase (Ewen, 1994;Weinberg, 1995;Paggi et al, 1996;Mulligan and Jacks, 1998). Indeed, in addition to the cell cycle, the RB family proteins regulate a wide spectrum of complex biological phenomena, as differentiation, embryonic development, apoptosis and senescence ( (Riley et al, 1994;Sidle et al, 1996;Herwig and Strauss, 1997;Stiegler et al, 1998;Thomas et al, 2003;Liu et al, 2004;Kapic et al, 2006) and references therein). However, as mentioned above, the crucial function attributed to RB is its tumor suppressor capability, and some debates are still ongoing whether p107 or Rb2/p130 share with RB this key feature (Mulligan and Jacks, 1998;Classon and Dyson, 2001; Paggi and Giordano, 2001).…”
Section: And References Therein)mentioning
confidence: 99%
“…p53 binds BAF53, and SWI/SNF activity is necessary for p53-mediated transcription activation and p53-mediated cell cycle control (Bochar et al, 2000;Wang et al, 2007). It has been reported that p53-mediated cell cycle arrest is dependent upon the RB family member p130 (Claudio et al, 2000;Gao et al, 2002;Kapic et al, 2006), which is known to bind BRG1 and BRM, and, by analogy with RB1, is likely to require SWI/SNF activity for function. Thus, the role of SWI/SNF in p53-mediated checkpoint control is likely to involve both p53 itself as well as downstream effectors of p53 signaling such as p130.…”
mentioning
confidence: 99%